Effect of Varying Levels of Nitrogen on the Growth and Yield of Muskmelon (Cucumis melo L.) - Niaz Ahmed Wahocho; Aftab Ahmed Maitlo; Qadir Bux Baloch; Arshad Ali Kaleri; Lubna Bashir Rajput; Naheed Akhtar Talpur; Zeeshan Ahmed Sheikh; Fida Hussain Mengal; Safdar Ali Wahocho (Journal of Basic & Applied Sciences, 2017)
Nitrogen (N) fertilization at higher rates enhances the yield of crop plants; however, overuse of N in cultivation of crop not only decreased Nitrogen Use Efficiency of crop plants but caused severe environmental pollution. Hence, the optimum use of N is perquisite for sustainable development of Agriculture. This study was carried out during 2016, to evaluate the effect of various nitrogen applications on the economic performance of muskmelon. This research work was laid out at experimental site of Horticulture orchard SAU Tandojam with three replications in RCBD. The growth and yield performance of muskmelon was assessed by using six nitrogen (N) levels viz; 0, 30, 60, 90, 120 and 150 kg ha-1. Two varieties including Chandny and golden tumbro were used in the current study.The result showed that effect of different nitrogen doses on the economic important parameters of muskmelon was significant (P<0.05) for all the studied traits. The crop fertilized with maximum N had positive effect on vegetative traits and produced tallest plants with more branches. Nitrogen also showed significant effects on fruits characteristics and produced plants with more fruits, highest weight and maximum yield. The results further reflected that there was a significant reduction in all vegetative and fruit contributing characters with each reduction in N application rate. The cultivars revealed a highly significant response to various N doses. The variety Golden Tumbro showed maximum vine length (201.00 cm), more branches vine-1 (3.4222), more fruit vine-1 (6.7339), highest fruits weight vine-1 (3.0056), maximum single fruit weight (656.83 g), fruit yield plot-1 (4.4450 kg) and fruit yield (24.635 t ha-1).